Case report: A severe myositis mimicking bulbar palsy after administration of immune checkpoint inhibitors - Rochigneux, Philippe; Bertucci, Alexandre; Loir, Elika; Mattei, Alexia; Robert, Danielle; Dassa, Michael; Chanez, Brice; Ebbo, Mikael; Gaigne, Lea; Chretien, Anne Sophie; Corazza, Giovanni; Schleinitz, Nicolas (Frontiers in Immunology, 2025)
ObjectivesImmune Checkpoint Inhibitors (ICI) are nowadays a cornerstone of anti-cancer treatments. However, the wide spectrum of immune-related adverse events (irAEs) represents a challenge in the oncological practice. Our objective is to document rare complications of ICI to help the community of onco-immunologists.MethodsWe reported the case of a severe myositis mimicking bulbar palsy treated in our Medical Oncology Department together with Internal Medicine Department. We present the clinical work-up (neurological exam, capillaroscopy) and the diagnostic tests (myositis specific and associated antibodies, nerve conduction study, electromyography) leading to this diagnosis. We also discussed the elimination of differential diagnoses (notably with normal MRI and cerebrospinal fluid analysis) and finally the clinical management of this severe irAE.ResultsA 57 years woman presented multiple sub-diaphragmatic adenopathies related with an advanced melanoma of unknown primary. She started a treatment with Ipilimumab (Ipi, anti CTLA-4) and Nivolumab (Nivo, anti PD-1) and presented at day 10 a grade IV myositis mimicking bulbar palsy with dysphonia, dysarthria and aphagia. In a multidisciplinary setting, she was treated with IV corticosteroids (methylprednisolone 1 mg/kg started at day 10, with a progressive decrease until 1 mg of prednisone in March 2024), IV immunoglobulins started at day 18 (1.5 g/kg in 2 days, administered monthly, with a progressive decrease and a cessation in June 2022), enteral nutrition, speech therapy and physical therapy, with noticeable improvement. After 4 years of follow-up, and only one infusion of Ipi/Nivo, the melanoma is still in complete response.ConclusionWe report an ICI-induced severe myositis mimicking bulbar palsy after the administration of Ipi/Nivo. The diagnosis and clinical care management of this rare complication requires a multi-disciplinary work-up.